Study of Formulation and Quality Characteristics of Jam Slice from Seaweed (Gracilaria sp.) with The Addition of Strawberry Fruit - Mukhaimin, Iman; S.T. Panjaitan, Pola; Adi, Catur Pramono; Alavia, Rohma (Politeknik Ahli Usaha Perikanan, 2024)
The purpose of the study was to determine the best formulation of seaweed pulp and strawberry pulp mixture in making jam slice based on the level of consumer preference for jam slice through hedonic tests, chemical quality characteristics, microbiological quality, and physical quality of jam slice. The production of jam slice from seaweed with the addition of strawberry fruit was carried out with several formulations of seaweed and strawberry fruit ratio, namely F1 (50:50), F2 (52.5:47.5), and F3 (55:45). The data were analyzed using One-way ANOVA, Kruskal Wallis non-parametric and descriptive tests. The results showed that there were no significant differences at the 5% significance level (p<0.05) on the parameters of appearance, aroma, taste, and texture. The best formulation with the highest mean value in making sheet jam is F2 with a composition of 52.5% seaweed; 47.5% strawberry fruit produces the highest level of panelist preference with an average value of appearance parameters of 7.28 (like), taste 7.16 (like), aroma 6.86 (like) and texture 7.12 (like).The chemical quality characteristics of formulation 2 have a moisture content of 40.23% which is higher than SNI-3746-2008, the fiber content is 7.413% and its antioxidant activity has an IC50 value of 0.67%. Furthermore, microbiological quality with a Total Plate Number (ALT) value of 3.04 x 10⁵ which is higher than SNI-3746-2008 and physical quality of texture (hardness) of 397.340974 gf.